Agentes poliaminérgicos modulam a extinção do medo condicionado contextual em ratos - Gomes, Guilherme Monteiro (2009)
Polyamines, such as spermidine and spermine, have been reported to improve memory retention through the activation of N-methyl-D-aspartate receptors (NMDAr). However whether polyamine agonists and antagonists alter extinction remains unclear. In the current study, we investigated whether spermidine and polyamine antagonists that selectively block the NR2B subunit at the NMDAr alter the extinction of contextual conditioned fear in male Wistar rats. While the bilateral intrahippocampal administration of exogenous spermidine (2 nmol/site) facilitated the extinction of fear conditioning, the injection of the antagonists arcaine (0.2 nmol/site), ifenprodil (20 nmol/site) and traxoprodil (0.2 nmol/site), disrupted fear extinction. NMDAr antagonists, at doses that had no effect per se, reversed the facilitatory effect of spermidine on fear extinction. These results suggest that exogenous and endogenous polyamines facilitate the extinction of contextual conditioned fear through activation of NR2B subunit-containing NMDAr in the hippocampus. Since extinction-based exposure therapy is widely used as treatment for a number of anxiety-related disorders, including phobias and post-traumatic stress, the currently reported facilitation of extinction by polyaminergic agents suggest these compounds as putative candidates for drug development.